Fatigue, sleep disturbance and the desire to die as an adverse impact of the COVID-19 survivors - Ellis Rochayati; Grace Noviana Chandra; Lely Setyawati Kurniawan; Angelina Tulus; Ida Ayu Kartika Widiadnyani (Journal of Clinical and Cultural Psychiatry, 2023)
A significant depressed episode called postoperative delayed paradoxical depression interferes with the disease's medical management and treatment. Because it occurred following a successful intervention, yet the patient didn't feel relieved, it is considered paradoxical. Often regarded as a mild variant of post-traumatic stress disorder, is said to be delayed due to the manifestation of several weeks after surgery. Anomalies or dysregulation of aminobiogenic metabolites, including norepinephrine, dopamine, and serotonin, are present in patients with mood disorders. The neurotransmitters norepinephrine, dopamine, and serotonin are reduced in depressive situations. Neurotransmitter norepinephrine controls mood, appetite, reward behavior, arousal, and drive. A neurotransmitter called dopamine controls motivation, pleasure, sex, and psychomotor function. Psychopharmaceuticals, psychotherapy, and neurostimulation are some of the therapeutic methods available for depression therapy. Serotonin and norepinephrine are increased at the postsynaptic level by SNRIs by blocking their reuptake. Besides psychopharmaceuticals approach, other methods include antidepressants, re-education, and psychotherapy are required.